ANALISIS KUALITAS JARINGAN NIRKABEL DENGAN METODE QUALITY OF SERVICE (Studi Kasus : BAPEDA PROVINSI SUMATERA SELATAN ) - Misinem, Misinem; Praja Mukti, Gerry (Jurnal Bina Komputer, 2021)
Information technology networks are growing rapidly, especially in computer networks using wireless. Wireless computer networks support various human jobs in communicating using the internet, such as uploading files or downloading files. To carry out these activities, we need a good wireless network in its services. To find a condition of a wireless network functioning properly, we need a method to measure it. The method that can be used is Quality of Services (QoS). QoS is a method that uses several indicators to measure the quality of a wireless network. These indicators are bandwidth, delay, and packet loss. The results showed that the measurement of wireless networks on BAPEDA Provinsi Sumatera Selatan shows good quality. The TYPHON version indicator indicates this, the delay value is below 150 ms, and the packet loss is 0%